Effet du sirop de caroube sur les aptitudes fermentaires et le développement des bactéries lactiques sur milieu lait écrémé - BOUZIANE NABIL (My University, 2014)
An experimental strain of Bifidobacteria (BL42) was cultivated in the presence of 5 and 10% of carob Juice as prebiotic. The growth and acidity kinetics were studied, also the viability and pH evolution during conservation at 4⁰C for 28 days in both pure and mixt culture with Streptococcus themophilus and/or Lactobacillus delbrueckii subsp bulgaricus. The results showed that 5 and 10% of carob juice stimulated the growth of BL42. The growth and acidity of both lactic bacteria were improved with 5% of carob. While in the mixt culture, the coagulation time was almost the same with the control. The addition of 10% of the carob affect badly the growth of L. bulgaricus but St. Thermophilus was stimulated in pure culture and inhibited in coculture. In the post acidification, the addition of carob juice maintains the viability of these strains.
Keywords: Carob juice- lactic bacteria-viability-conservation